An Analysis of the Effect of Roadway Design on Driver’s Workload - Orazio Pellegrino (The Baltic Journal of Road and Bridge Engineering)
Driving behaviour is a direct consequence of the stimuli received from the road infrastructure, from the surrounding environment and from the atmosphere inside the vehicle. Almost all of these perceptions, which affect steering, are received through the drivers’ eyes. For this reason, in this paper visual behaviour was examined in order to deduce new indexes connected to mental workload. To this aim, a consistent sample of drivers covered a rural road inside a vehicle, while their eye movements and driving activities were being recorded with suitable instruments. The quantification of some variables involved in the trials permitted the evaluation of visual behaviour and determination of a measure of mental workload, identifying also any situations where performance was compromised. Some reports between mental workload and road geometry, summarized in a few tables, could represent a further aid for road designers and managers.